A synopsis of sloanea (Elaeocarpaceae) in the neotropical extra–amazonian region - Sampaio, Daniela [UNESP]; Souza, Vinicius Castro (My University, 2016)
The genus Sloanea is comprised of 150 species, of which about 50 occur in Brazil among several vegetation types but mainly the Amazon and Atlantic forests. The present work provides a synopsis of the Neotropical species of Sloanea in the extra–Amazonian region based on a recent revision of the genus. In general, morphologically Sloanea comprises large trees endowed with buttressed roots; simple leaves; flowers with sepals that may or may not cover the reproductive organs in pre–anthesis phases; stamens with the connective prolonged into an awn that is acuminate, acute or aristate and fruit covered with rigid or flexible bristles or sometimes unarmed. This synopsis describes 17 species, and provides an identification key, illustrations and comments on their diagnostic characters, geographical distribution and main bibliographic references.
Keywords: Atlantic forest; Brazil; Diversity; Savanna; Taxonomy